Bullying Behaviour among In-school Adolescents: Assessing the Predictability of Personality Traits and Self-Esteem - Taofeeqah O. Olaniyan; Esohe G. Ehondor; Olubunmi O. James; Emmanuel E. Uye (International Journal of Technology and Education Research, 2025)
Bullying behaviour has remained a global issue with far-reaching consequences on their psychological well-being, social relationships, and academic performance among victims. Studies linking personality traits and self-esteem on bullying behavior within specific cultural contexts are lacking. Therefore, this study examined the predictive ability of personality traits and self-esteem on bullying behaviour among in-school adolescents in Ibadan North Local Government Area. Cross sectional survey design was adopted while purposive sampling technique was used to select the study location. Data were collected from 387 participants using validated scales and analyzed using multiple regression analysis and independent samples t-test to test two hypotheses that were accepted at p < 0.01 level of significance. The result demonstrated that personality traits and self-esteem jointly predicted bullying behavior among study participants [R² = .082, F(6, 380) = 5.66, p < .01]. In addition, the results revealed that agreeableness (β = .24, t = 4.58, p < .01) and conscientiousness (β = -0.12, t = -2.37, p < .01) independently predicted bullying behavior among study participants. However, self-esteem, extraversion, openness to experience and neuroticism did not independently predict bullying behavior among study participants. The novelty of the study is that it is the first time bullying behaviour is studied in a specific cultural milieu in Ibadan. It is recommended that a comprehensive, personality-focused anti-bullying programs be designed and implemented to reflect the cultural and educational contexts among in-school adolescents.